Dwelling in the Digital Age - Antoine Picon (Footprint)
Dwelling appears as a complex entanglement of dreams and realities, mental representations, and concrete practices. Here the question of its evolution in the digital age is approached at three levels. Firstly, what are the changes that it brings to the concrete experience of the built environment that have accompanied the rise of digital technologies? The Covid19 pandemic has contributed to reveal some of them, but the full picture is still far from clear. Secondly, how are these changes related to this different understanding of the human that is often dubbed as a transition towards a ‘posthuman’ condition, Thirdly, the least evident to address: will these shifts lead to the emergence of new spatial organizations and programs? Central to the argument developed here is that there is a deep relation between dwelling and the constitution of human subjectivity. Dwelling in the digital age is thus inseparable from the question of the evolution of what it means to be human in our contemporary societies.